HPLC-MS/MS Method for Quantitation of Sildenafil and Its Active Metabolite in Human Plasma - G. G. Rodionov; I. I. Shantyr; I. E. Ushal; E. V. Svetkina; E. A. Kolobova; K. A. Zakharov (Регуляторные исследования и экспертиза лекарственных средств, 2020)
A high demand for sildenafil-based drugs puts a premium on the development of methods for quantitation of sildenafil in bio-substrates to facilitate pharmacokinetic analysis in bioequivalence studies. High performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) was proposed for the method development due to its high sensitivity, selectivity, reproducibility, and performance. The aim of the study was to develop and validate an HPLC-MS/MS method for quantitative determination of sildenafil and its active metabolite N-desmethyl sildenafil in human plasma. Approbation of the developed technique in the study of the pharmacokinetic profiles of sildenafil and N-desmethyl sildenafil in healthy volunteers in the study of the bioequivalence of the drug sildenafil in the form of a spray. Materials and methods: the method was implemented using the Agilent 1200 high-performance liquid chromatography system with the Agilent 6440 triple quadrupole system, and Poroshell 120 EC-C18 chromatographic column, 4.6 m × 150 mm × 2.7 μm. Calibration samples were prepared using sildenafil citrate and N-desmethyl sildenafil reference standards with 99.5 and 98.5% purity, respectively. Vardenafil was used as an internal standard. Pharmacokinetic profiles of sildenafil and N-desmethyl sildenafil were studied in 44 healthy male volunteers as part of a bioequivalence study approved by the Ministry of Health of the Russian Federation. The primary data processing was performed using Mass Hunter software version B 06.00, and statistical processing was performed using Microsoft Office Excel 2010 and Statistica 6.1. Results: the authors developed and validated a method for quantitation of sildenafil and its active metabolite N-desmethyl sildenafil in human plasma. The developed method was used successfully to study pharmacokinetic profiles of the discussed compounds in healthy volunteers. Conclusions: the developed method of quantitative determination of sildenafil and its active metabolite N-desmethyl sildenafil in human plasma is simple, reproducible, fast, and robust. The results of the pharmacokinetic studies using the developed method demonstrated bioequivalence of the test product and the reference product.